2021
DOI: 10.1007/s12274-021-3609-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nano-scale pore structure and organic amine assembly in porous silica on the kinetics of CO2 adsorptive separation

Abstract: Nano structure including pore structure and amine assembly is critical for improving sorption and desorption kinetics for adsorptive CO 2 separation. The present work delineates (1) the influence of the nano-scale pore structure of amine-functionalized solid sorbents, and (2) effect of changing the assembly of amine molecules on surface of nano-porous SiO 2 on the rates of adsorption and desorption of CO 2 . 50PEI-MSN sorbent with inverted cone-shaped pores was prepared by using mesoporous silica nanospheres (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Consequently, the 3-D MBSs exhibited a significantly higher CO 2 sorption capacity and a faster sorption rate compared with those of 1-D MBSs (Figure A). Additionally, the temperature dependence on 3-D MBS is much less than that of 1-D MBS, which can also be attributed to the 3-D pore structure facilitating CO 2 diffusion and promoting PEI dispersion (Figure B; the definition and details of the number of PEI coverage layers can found in ref ).…”
Section: Development and Application Of Mbssmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the 3-D MBSs exhibited a significantly higher CO 2 sorption capacity and a faster sorption rate compared with those of 1-D MBSs (Figure A). Additionally, the temperature dependence on 3-D MBS is much less than that of 1-D MBS, which can also be attributed to the 3-D pore structure facilitating CO 2 diffusion and promoting PEI dispersion (Figure B; the definition and details of the number of PEI coverage layers can found in ref ).…”
Section: Development and Application Of Mbssmentioning
confidence: 99%
“…(C) Normalized sorption capacity of 2N-CSD, PEI-50/MSN, and PEI-50/SBA-15 at 30 °C (insets: TEM and SEM images of PEI-50/MSN). (D) Schematic illustration of CO 2 sorption over 2N-CSD, PEI-50/MSN, and PEI-50/SBA-15 sorbents [reproduced with permission from ref , copyright 2021 Springer].…”
Section: Development and Application Of Mbssmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica (SiO 2 )-based materials have garnered significant attention for their capability to improve CO 2 capture. Their high surface area, nanopore sizes, , and chemical stability render them ideal for CO 2 absorption. , Goeppert et al conducted a study on CO 2 adsorption using polyethylenimine (PEI M w 25000) deposited on fumed SiO 2 . The study found that the sample with 50 wt % PEI had a higher adsorption capacity of 1.71 mmol/g.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethyleneimine (PEI) has high CO 2 absorption capacity, which is used as a modifier to modify silica for improving CO 2 adsorption performance and selectivity. , The most commonly used method for constructing amine-silica adsorbents is the solvent impregnation method, in which amine can be uniformly dispersed on the silica. However, the silica with high amine loading is easy to agglomerate, and the use of organic solvents for dispersion also increases the production cost.…”
Section: Introductionmentioning
confidence: 99%